Cross-Sector Collaboration, Organizational Commitment, and Service Innovation in the Premarital Counseling Program - Desi Masri; Juhari Juhari; Afrizal Afrizal (Publik : (Jurnal Ilmu Administrasi), 2025)
Premarital counseling programs play a pivotal role in fostering the development of quality families and preventing stunting at its roots. However, the implementation of these programs faces significant challenges, including low community engagement, insufficient cross-sector synergy, and limited service innovation. This study aims to investigate the influence of cross-sector collaboration, organizational commitment, and service innovation on the effectiveness of premarital counseling programs, with community participation acting as a mediating variable. A quantitative research design was employed, utilizing a survey administered to prospective couples undergoing premarital counseling conducted by relevant officers in the Bangka Belitung Islands Province. Data were analyzed using Structural Equation Modeling (SEM)-Partial Least Squares (PLS) to assess the interrelationships among the variables. The findings indicate that cross-sector collaboration, organizational commitment, and service innovation significantly enhance community participation and, consequently, the effectiveness of premarital counseling programs. Furthermore, community participation was found to significantly mediate the relationship between the independent variables and program effectiveness, thereby amplifying their impact. This research contributes to the literature by advancing the understanding of the role of cross-sector collaboration, organizational commitment, and service innovation in public service delivery, and highlights the critical importance of strengthening community participation as a strategic approach to improving the effectiveness of premarital counseling programs in fostering quality families